Enhancing entrepreneurial skills of persons with disabilities (PWDs) through immersive learning in the metaverse: a design thinking approach. - Adarkwah, Michael Agyemang; Islam, A.Y.M. Atiquil (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: The double threat of unequal job opportunities for persons with disabilities (PWDs) and the lack of professional training to use innovative technologies at work have led to multiple calls to promote inclusivity at work. PWDs are underrepresented in the workforce and often face discrimination by employers. One way PWDs have responded to their limited employment within organisations is by pursuing self-employment or business creation. Higher education institutions (HEIs) and technical and vocational education and training (TVET) institutions are expected to embrace new pedagogies facilitated by digital technologies to promote creativity in business among PWDs. While many studies have explored the potential of entrepreneurship education in equipping PWDs with the requisite skills and knowledge to become successful entrepreneurs, the aspect of technology has been largely overlooked. In this study, we employ a design thinking (DT) approach to propose a metaverse-based entrepreneurship education for disabilities (MEED) framework aimed at fostering inclusive innovation and entrepreneurship for vulnerable populations such as those with disabilities. Results: By leveraging metaverse technology based on the DT principle of empathy, entrepreneurship education for PWDs can be transformed to create lifelong learning opportunities. This approach enables seamless interactions and immersive learning experiences that support the educational needs of all learners. Implications: Different entrepreneurship learning opportunities and scenarios for different disabilities are presented. Future research areas and possible implications are also discussed. IMPLICATIONS FOR REHABILITATION: The metaverse in entrepreneurship education can enable teachers of PWDs to design learning environments that support emotional learning and eliminate challenges related to social identification and identity. Promoting metaverse-based entrepreneurship education provides lifelong opportunities for all vulnerable populations like PWDs, as enshrined in Sustainable Development Goal Four (SDG 4). Expanding the metaverse's technological infrastructure addresses accessibility and equity, enabling more users, transactions and activities without compromising the quality of the learning experience. Educators will need to create a disability-friendly environment in the metaverse by creating a learning scene or interface that PWDs can identify with.